Densely packed matrices as rate determining features in starch hydrolysis. Issue 1 (May 2015) - Zhang, Bin; Dhital, Sushil; Gidley, Michael J.
<x xml:space="preserve">Abstract</x> To aid in the design of starch-containing foods with slow and/or incomplete digestion in the upper gastrointestinal tract, the starch structural factors which control the rate of action of alpha-amylase are reviewed. It is concluded that local starch molecular density has the major influence on amylase digestion kinetics, and that density sufficient to either limit enzyme binding and/or slow down catalysis can be achieved by either crystallization or dense amorphous packing.